2014
DOI: 10.1089/scd.2013.0500
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic Bone Marrow Mesenchymal Stem Cell Transplantation in Patients with UDCA-Resistant Primary Biliary Cirrhosis

Abstract: The objective of this study was to evaluate the safety and efficacy of allogeneic bone marrow mesenchymal stromal/stem cell transplantation (BM-MSCT) for patients with ursodeoxycholic acid (UDCA)-resistant primary biliary cirrhosis (PBC). Ten patients were enrolled in this trial of BM-MSCT. All patients were permitted to concurrently continue their previous UDCA treatment. The efficacy of BM-MSCT in UDCA-resistant PBC was assessed at various time points throughout the 12-month follow up. No transplantation-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 40 publications
1
67
0
Order By: Relevance
“…MSCs can be obtained from not only bone marrow but also medical wastes such as adipose tissue [57,58], umbilical tissue [59][60][61][62], and dental pulp [63]. MSCs are positive for the common markers CD73, CD90, and CD105; however, they are negative for the endothelial marker CD31 and hematopoietic marker CD45 [56,64].…”
Section: Mscsmentioning
confidence: 99%
See 1 more Smart Citation
“…MSCs can be obtained from not only bone marrow but also medical wastes such as adipose tissue [57,58], umbilical tissue [59][60][61][62], and dental pulp [63]. MSCs are positive for the common markers CD73, CD90, and CD105; however, they are negative for the endothelial marker CD31 and hematopoietic marker CD45 [56,64].…”
Section: Mscsmentioning
confidence: 99%
“…In the field of liver cirrhosis, as shown in Table 1, many autologous [70][71][72][73][74][75][76][77][78][79][80][81][82][83] and four allogeneic [59][60][61][62] MSC therapies involving a variety of tissue origins and administration routes have been reported. Although details regarding the mechanisms of therapeutic effects in humans remain unclear, most studies have reported favorable effects with improvement in MELD scores, Child-Pugh scores, and some serum markers such as albumin and bilirubin.…”
Section: Mscsmentioning
confidence: 99%
“…Mesenchymal stem cell (MSC) transplantation is considered to be safe, and has been diffusely tested in autoimmune hepatic disease clinical trials with encouraging results[186,187]. MSC transplantation could modulate the systemic immune response and promote recovery in hepatic inflammation of PBC[186,187].…”
Section: Therapy Of Pbcmentioning
confidence: 99%
“…Of these retrieved studies, 202 were excluded because of animal experiments, reviews, or insufficiently detailed data. Overall, we identified and included 17 publications involving 20 studies that met the inclusion criteria (11,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). There were five papers that involved two studies.…”
Section: Study Selectionmentioning
confidence: 99%